Clinical value of plasma and peripheral blood mononuclear cells Epstein–Barr Virus DNA dynamics on prognosis of allogeneic stem cell transplantation - Zhou, Xi; Lu, Xuan; He, Jing; Xu, Ziwei; Li, Qian; Ye, Pian; Zhong, Zhaodong; Shi, Wei; Yan, Han; You, Yong; Hu, Yu; Wang, Huafang (Frontiers in Cellular and Infection Microbiology, 2022)
The application of intracellular and extracellular Epstein–Barr virus (EBV) DNA in allogeneic hematopoietic stem cell transplantation (allo-HSCT) has been poorly characterized. We conducted a combined prospective-retrospective study of 300 patients who underwent allo-HSCT between 2016 to 2019 in our center and monitored for EBV DNA within the first year after HSCT. Combining the optimal cut-off value of EBV DNA load (7.3×104 copies/106 cells) in PBMCs (peripheral blood mononuclear cells) and qualitative detection in plasma (400 copies/mL) allowed for the better differentiation of EBV-related posttransplant lymphoproliferative disorders (EBV-PTLD), with increased sensitivity (100%) and specificity (86%), and provided the effective risk stratification of EBV DNA level according to their impact on transplant outcomes. By multivariate analysis, patients with intermediate-level of EBV DNA load (low EBV DNA load in PBMCs or high load in PBMCs but negative in plasma) was associated with superior overall survival (HR 1.92, 95% CI 1.03-3.57, p=0.039) and lower transplant-related mortality (HR 3.35, 95% CI 1.31-8.58, p=0.012) compared to those with high-level (high load in PBMCs and positive in plasma). Notably, high EBV-level group had poor reconstitution of CD4+ and CD8+T cells, and both low and high EBV-level groups showed abnormally increase in IL-10 level within one year. Additionally, patients with peak EBV DNA load in PBMCs during 3-12 months had a higher incidence of chronic graft versus host disease (GVHD) than those within 3 months post transplantation (17.4% vs 13.7%, p=0.029). Collectively, EBV DNA in PBMCs can synergistically predict the risk of EBV-PTLD and GVHD. The intermediate-level of EBV DNA presented in plasma and PBMCs might contribute to a better reconstitution of T cells associated with favorable prognosis of allo-HSCT.